Oblicza współczesnych organizacji polonijnych w wybranych krajach unijnej piętnastki - Czop, Edyta (Polityka i Społeczeństwo, 2021)
The article deals with issues to do with organizational life of the Polish milieus in the “old” Member States of the EU-15. It is predominantly focused on the most recent forms of the Poles’ activity which used to be considered an absolute novelty just a few years ago. This is exemplified by a functional analysis of women’s organizations, self-help groups as well as organizations grouping top class specialists. The Author tries to explain the reasons why the Poles flowing into the EU countries try to resolve their problems by themselves. Also, the Author attempts to answer the question why old Polonia organizations are not always able to respond effectively to the recent migrant community needs.